Harmonic Index of Bridge and Chain Graphs - J. Amalorpava Jerline; K. Dhanalakshmi; L. Benedict Michael Raj (International Journal of Mathematics And its Applications, 2017)
The harmonic index $ H(G) $ of a graph $ G $ is defined as the sum of the weights $ \dfrac{2}{d(u)+d(v)} $ of all edges $ uv $ of $G$, where $d(u) $ denotes the degree of the vertex $u$ in $G$. In this work, we obtain harmonic index of bridge and chain graphs. Using these results, harmonic index of chemical graphs are computed.